Clinical and circulating biomarkers of survival and recurrence after radiofrequency ablation in patients with hepatocellular carcinoma. (September 2018) - Canale, Matteo; Ulivi, Paola; Foschi, Francesco Giuseppe; Scarpi, Emanuela; De Matteis, Serena; Donati, Gabriele; Ercolani, Giorgio; Scartozzi, Mario; Faloppi, Luca; Passardi, Alessandro; Tamburini, Emiliano; Valgiusti, Martina; et al.
Abstract: Radiofrequency ablation (RFA) is an effective local treatment for curative intent in patients with cirrhosis of the liver and hepatocellular carcinoma (HCC) with diameter <3 cm. Several meta-analyses have shown that RFA and surgical resection are comparable in terms of their impact on overall survival. The only clinical data available on markers that are predictive of recurrence and survival after RFA treatment are based on retrospective observational studies. Prospective randomized trials are thus needed to further research in this area. In the present review we analyzed a number of clinical factors that are considered to predict recurrence or survival in HCC patients treated with RFA. We also discussed in detail the circulating biomarkers investigated to date, together with their potential to predict prognosis and recurrence after RFA therapy. Overall survival rates of patients with HCC are significantly affected by liver function, defined as Child-Pugh class, high baseline serum alpha-fetoprotein levels, and the presence of portosystemic collaterals. However, the development of local tumor progression does not significantly affect overall survival. This result is achieved by the effective therapies in patients who relapse after treatment with RFA. For this reason there is an urgent need to identify new circulating biomarkers.